Uma abordagem para o 'também'-aditivo do Português Brasileiro - Cipolli, Matheus Bittencourt (2022)
The main goal of the present master thesis is to define, within the model of formal semantics of natural languages, one of the main uses of ‘também’ in Brazilian Portuguese, which we call additive-‘também’. For a detailed and comprehensive definition of this use, it is necessary to mobilize several different researches of the relevant areas, such as the analyses of ‘too’ in Green (1968), Kaplan (1984), Krifka (1990) and Amsili, Beyssade et al. (2010) as well as the analyses of coordination found in Winter (2006) and Zhang (2014), which help to describe the additive component of the object of this research. The process of describing ‘também’ additionally mobilizes discussions of presupposition and, in particular, of anaphora, which represents a fundamental part of the additive function of ‘também’. In the course of this work, such previous research will be contemplated and will offer a perspective necessary for the analysis of additive- ‘também’, in particular for the points of intersection that demonstrate the most inherent parts of the functioning of that item. In possession of this perspective and in association with the original proposals of this work a more comprehensive description will be offered than the previous ones without sacrificing the economy of the model.